The Catholic Gen-Z on Virtual Eucharist Within the Archdiocese of Pontianak - Angga Satya Bhakti; Bernardus Ario Tejo Sugiarto; Cenderato Cenderato; Abil Rudi (Al-Albab, 2025)
Since the expiration of the Community Activities Restrictions Enforcement on 13 December 2022, The Catholic Church has also resumed in-person (offline) Eucharistic celebrations. Virtual Eucharistic celebrations continue in select parishes, particularly within the Archdiocese of Pontianak. This study examines how Catholic Generation Z (Gen-Z) individuals— a cohort inherently familiar with the virtual world—respond to virtual versus in-person Eucharistic celebrations. From the perspective of liturgical theology, the Eucharist should ideally be celebrated in person unless circumstances necessitate a virtual format. This study employs a quantitative approach with an online questionnaire sent via WhatsApp to 250 Catholic Generation Z respondents in several parishes. The results show that although offline Mass was rated as spiritually better, practical conditions made online Masses also preferred by the majority of respondents. This research provides insights for the Catholic Church in the Archdiocese of Pontianak in formulating pastoral approaches that better suit the spiritual and practical needs of Generation Z in the context of multicultural society of Pontianak.